ableitung, h-methode

... komplette Frage anzeigen

1 Antwort

Du meinst f(x) = 1/wurzel(x), oder?

1/h * (f(x+h)-f(x)) = 1/h * (1/w(x+h) - 1/w(x))

= (erweitern) 1/h * (w(x)-w(x+h))/(w(x+h) * w(x))

= (erweitern) 1/h * (w(x)-w(x+h)) * (w(x)+w(x+h)) / (w(x)+w(x+h)) / (w(x+h) * w(x))

= 1/h * (x-(x+h)) / (w(x)+w(x+h)) / (w(x+h) * w(x))

= 1/h * (-h) / (w(x)+w(x+h)) / (w(x+h) * w(x))

= -1 / (w(x)+w(x+h)) / (w(x+h) * w(x))

-> -1 / (w(x)+w(x)) / (w(x) * w(x))

= -1/(2w(x)) / x

= -1/2 * 1/w(x)^3 = -1/2 * x^(-3/2)

Antwort bewerten Vielen Dank für Deine Bewertung

Was möchtest Du wissen?